Simulation and experimental study of FBG-based magnetic field sensors with Terfenol-D composites in different geometric shapes. (February 2021) - Lopez, Juan D.; Dante, Alex; Carvalho, Cesar C.; Allil, Regina C.S.B.; Werneck, Marcelo M.
Highlights: Optical magnetic field sensors based on magnetostrictive composites in different shapes were characterized. Magnetostrictive composites of Terfenol-D can be easily molded in different shapes. A tiny magnetic field sensor using only 0.052 g of Terfenol-D showed the higher sensitivity. The particular shape of the sensor is a decisive parameter in its sensitivity. A temperature-compensating sensor probe and method were proposed. Abstract: In this paper, we report a study on optical sensors based on fiber Bragg gratings (FBG) and magnetostrictive composites of Terfenol–D applied to magnetic field measurement. The study consisted in determining the sensor's sensitivity influenced by the shape of the magnetostrictive composite with an embedded FBG. The proposed sensors were designed and simulated using finite element method (FEM) in cylindrical, hyperbolic, and conical shapes in order to determine the geometric configuration for best sensitivity using the less amount of Terfenol-D. One prototype of each designed shape was manufactured using powdered Terfenol-D with 200–300 µm grain size and epoxy resin. The experimental results showed that the shape of the magnetostrictive composite influences up to 59% in the sensitivity of the sensors. The results also showed that the smaller sensor, a ∅1.5 mm × 16 mm cylinder using only 0.052 g of Terfenol-D was the best shape and achieved the highest sensitivity.